Oral anticoagulants for the treatment of venous thromboembolism and non-valvular atrial fibrillation: a cost analysis - Isabella C DENARDIN; Helena H. BORBA; Antonio M. MENDES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To analyze the total direct cost of anticoagulant therapies indicated for the chronic treatment of patients with non-valvular atrial fibrillation (AF) and the acute treatment of venous thromboembolism (VTE) in the perspective of a tertiary teaching hospital and the national public health system. Methods: Therefore, the review of the treatment regimens that included all the oral anticoagulants based on nationals and internationals guidelines. The cost data were extracted and performed the simulation of the costs of pharmacological therapy and exams for monitoring therapeutic goals. The time horizon was defined by 365 days for AF and 90 days for TEV. Results: The treatment cost of 90 days in VTE was: rivaroxaban (USD $82,96 to USD $156,15), apixaban (USD $110,25 to USD $123,11), edoxaban (USD $106,56 to USD $265,15), dabigatran (USD $150,71 to USD $249,98) and warfarin (USD $54,94 to USD $159,66). While the treatment cost of AF was: rivaroxaban (USD $270,35 to USD $508,89), apixaban (USD $414,86 to USD $463,26), edoxaban (USD $402,41 to USD $477,78), dabigatran (USD $414,86 to USD $416,24) and warfarin (USD $20,03 to USD $43,54). Conclusion: Warfarin presented the lowest treatment cost for both comorbidities. However, although direct oral anticoagulants (DOACs) are always associated with higher price ranges, were observed price ranges in VTE treatment where DOACs proved to be economically more advantageous than warfarin, still requiring complete economic assessments.